Co-administration of GnRH-agonist and hCG for final oocyte maturation (double trigger) in patients with low number of oocytes retrieved per number of preovulatory follicles-a preliminary report - Jigal Haas; Eran Zilberberg; Shir Dar; Alon Kedem; Ronit Machtinger; Raoul Orvieto (2014)
Recently, the co-administration of GnRH agonist and hCG for final oocyte maturation- 40 and 34 hours prior to OPU, respectively (double trigger) was suggested as the treatment of genuine empty follicle syndrome. In the present study, we aim to evaluate whether the double trigger improves the number of oocytes retrieved in patients with low (<50%) number of oocytes retrieved per number of preovulatory follicles.In this proof of concept cohort historical study, we compared the stimulation characteristics of 8 IVF cycles, which include the double trigger to the patients' previous IVF attempt, triggered with hCG-only.Patients who received the double trigger (study group) had a significantly higher number of oocytes retrieved, number of 2PN, number of embryos transferred and significantly higher proportions of the number of oocytes retrieved to the number of follicles >10 mm and >14 mm in diameter on day of hCG administration, with a tendency toward a higher number of TQE, as compared to their previous cycles (hCG-only trigger). Three ongoing clinical pregnancies were recorded in the study group and none in the hCG-only trigger group.Co-administration of GnRH-agonist and hCG for final oocyte maturation, 40 and 34 hours prior to OPU, respectively (double trigger), is suggested as a valuable new tool in the armamentarium for treating patients with low/poor oocytes yield despite an apparently normal follicular development and E2 levels and in the presence of optimal hCG levels on the day of OPU.